Perceived need for treatment associated with orthorexia nervosa symptoms. (August 2020) - Walker-Swanton, Faith E.; Hay, Phillipa; Conti, Janet E.
Abstract: Orthorexia Nervosa is characterised by a pathological fixation on food purity and nutrition, coupled with a severely restricted diet and avoidance of food believed to be unhealthy. Little is known about the risk factors associated with the condition or if the condition should be treated in a similar way to other eating disorders or whether distinct interventions are required. This study aimed to identify (1) putative variables of the need for treatment in those with orthorexia symptomology and (2) assess whether comorbid psychological symptomologies were associated with orthorexia nervosa. An online cross-sectional self-report survey was developed and the data of 130 participants analysed using regression analyses. As predicted, individuals with higher levels of orthorexic symptomology, eating disorder symptomology and those who identified their healthy eating as problematic were significantly more likely to have a perceived need for treatment, however those who self-identified as having a current or past eating disorder were not. Orthorexic symptomatology was significantly correlated with eating disorder symptomatology, obsessive-compulsive symptoms, anxiety, and depression, however in the regression analysis, eating disorder symptomatology was the only significant variable. These findings highlight the need to consider orthorexic symptoms in people with eating disorders and that this inter-relationship and the ego-syntonicity of symptoms may reduce help-seeking. Highlights: Orthorexia nervosa symptoms were associated with eating pathology Orthorexia nervosa symptoms were not associated with depression, anxiety and obsessive-compulsive tendencies Perceived need for treatment increased with higher orthorexia and eating disorder symptomology Perceived need for treatment increased in those who identified their eating behaviours as problematic